Obtaining tissues and organs for transplantation and coronavirus infections: a scoping review - João Luís Erbs Pessoa; Neide da Silva Knihs; Aline Lima Pestana Magalhães; Sibele Maria Schuantes Paim; Laísa Fischer Wachholz; Bartira de Aguiar Roza
ABSTRACT Objectives: to map the care recommendations available in the literature capable of supporting health professionals' decision-making in the organ and tissue donation process before the COVID-19 pandemic. Methods: is a nine-step scoping review with searches performed in three databases and an electronic library (Science Direct). Results: 873 publications were retrieved, 15 selected for analysis. All were published in 2020, originating mainly on China, with predominance of original articles. The most frequent recommendations relate to testing to detect SARS-CoV-2 infection for deceased donors (52.6%) and clinical evaluation of potential donors and possible donors (31.6%). Final considerations: it is believed that the recommendations evidenced will support health professionals in the process of donation and organ transplantations to determine interventions for decision-making during the COVID-19 pandemic.